Avaliação do paciente crítico no centro de terapia intensiva por acadêmicos de enfermagem : aprendizagem por simulação - Gomes, Roberta Garcia (2018)
Introduction: The basis of a safe care by the intensive care nurse is the clinical evaluation of the critical patient. The competency conformation starts at the undergraduate level and the professor has the role of facilitating the learning teaching process to meet the National Guidelines for the nursing undergraduate course, aiming at the formation of a professional with a qualified insertion in the job market. In this perspective, Clinical Simulation is increasingly used in the nursing course, as an active methodology, since the student is at the center of learning, contributing actively to the construction of knowledge. Objective: to analyze the competences conformed by the academic in the evaluation of the critical patient, from the clinical simulation. Method: Qualitative, analytical, deductive study, in the Cultural History section of Vygotsky. It was developed in stages involving three distinct scenarios: Clinical Simulation, in the Clinical Simulation Laboratory of a university in the south of Minas Gerais; Observation Participant in the adult Intensive Care Center (ICU) of a General Hospital, in the same municipality and Focal Group, in the Auditorium of the Hospital Institution. The participants were 14 undergraduate nursing students from a public university in the south of Minas Gerais. After approval by the Ethics Committee (CAAE 61544616.9.0000.5142), the data were collected with Objective and Structured Clinical Examination (OSCE), used in Participant Simulation and Observation, Data Collection Roadmap completed by the participants, Field Diary and Testimonials from the Debriefing and Focus Group. The data were organized in thematic categories, according to the Content Analysis, in the thematic modality and analyzed according to the concepts of the Cultural Historical perspective of Vygotsky. Results and discussion: Data analysis revealed the category "Ressignification of the process of caring critical patients in intensive care: learning by simulation" with two subcategories "Confrontation in crisis situations: personal experiences related to the training process" and "Conformation of competences: Mediation by the instruments and by the other ". In the first subcategory, several forms of confrontation are perceived by the students in the face of the experience of Clinical Simulation, such as nervousness and anxiety, but in the Cultural Historical perspective, the new demands offered by the medium stimulate the intellect so that reasoning can achieve higher stages. In the second subcategory it was possible to perceive the importance of qualified mediation for the viability of learning. In the category, it is understood that previous experiences and mediation contribute to the construction of knowledge and it was possible to perceive different levels of development of the academics. Conclusion: Simulation is an instrument that contributes to the viability of the teaching learning process by the nursing student. It is up to the professor to conduct a qualified mediation and to potentiate the area of proximal development of the academics in an individualized way, combining the pedagogical strategy with the clinical practice, since it is while doing in the real environment that the competence is consolidated.